CÓMO PROMOVER LA INVESTIGACIÓN E INNOVACIÓN CIENTÍFICA DESDE EL MODELO APOYO PEDAGÓGICO DE LA COORDINACIÓN DE ECONOMÍA DEL CENTRO DE SERVICIOS FINANCIERO SENA - Pérez Pertuz, Johemir
The following article is oriented to the description of the process to lead and motivate students of the Financial Services Center (CSF) SENA, towards scientific research and technological innovation through productive projects of social, environmental and knowledge nature. the reality that surrounds them with respect to their financial training area. The Pedagogical Project Support (PPP) strategy model is proposed, which will allow achieving the expected result, to motivate the student to start with genuine commitment, a scientific research either aimed at broadening their knowledge about their field of education or directed towards entrepreneurship whose indispensable component is innovation. The model of the structure of a consulting unit that seeks to facilitate students' learning research environments is proposed.